Pengembangan Sistem Manajemen dan Analisis Key Performance Indicator “Smart Kpi” Berbasis Web - Meiliana, Meiliana; Bryan, Bryan; Joshua, Felix; Raymond, Raymond (ComTech: Computer, Mathematics and Engineering Applications, 2014)
The goals of organization or company are achieved by the given objectives of all the employees. In order to measure the achievement of the employees, the organization or company can use Key Performance Indicator (KPI). However, most of the application of KPI is done manually, for example in inputting scores, result submission, score checking, and report creation. Seeing this condition, an application called “Smart KPI” is developed to provide an effective and efficient KPI System, to provide the valid KPI data to assist the monitoring of employees performance, and to create the organizational structure by relating the supervisor with the subordinate. This application is developed using Scrum research method that consists of backlog and sprint. The backlog consists of literature studies, comparing previous research or product, distributing questionnaires, and interviewing IT experts. Sprint consists of sprint and release planning and actual sprint work. The result is a PHP based web application for KPI processing for an organization or company that depends on the structure of users and indicators that have been set in the back-end and apply the settings and process the KPI in the front-end. The conclusion that obtained is this application will help the KPI processing which match the user requirement and has a good user interface and performance.